2013
DOI: 10.1016/j.powtec.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Alternative method for producing organic fertiliser from anaerobic digestion liquor and limestone powder: High Shear wet granulation

Abstract: Publisher rights This is the author's version of a work that was accepted for publication in Powder Technology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Powder Technology, VOL 233, 01/2013 General rights Copyright for the publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
2
27
0
1
Order By: Relevance
“…XRD and particle size analysis of the powders Limestone powder supplied by Kilwaughter Chemicals Ltd., UK, was used as one of the raw materials. X-ray diffraction (XRD) analysis of the powder limestone that it was mainly composed of calcite and quartz minerals [4]. Value tea purchased from Tesco was used as the second powder component in the granulation experiments.…”
Section: Materials Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…XRD and particle size analysis of the powders Limestone powder supplied by Kilwaughter Chemicals Ltd., UK, was used as one of the raw materials. X-ray diffraction (XRD) analysis of the powder limestone that it was mainly composed of calcite and quartz minerals [4]. Value tea purchased from Tesco was used as the second powder component in the granulation experiments.…”
Section: Materials Characterisationmentioning
confidence: 99%
“…[4]. In this procedure a sample of the granules (5 g) is subjected to attrition forces by shaking them mechanically on a sieve shaker and recording the mass loss as a function of time.…”
Section: Attrition Testmentioning
confidence: 99%
See 1 more Smart Citation
“…6). In the literature Mangwandi et al (2013) found that tensile strength is increasing with increasing impeller Fig. 7.…”
Section: Mechanical Propertymentioning
confidence: 91%
“…On the other hand, a material that in one type of industry is considered as waste, can be useful in another manufacturing process (Zhang et al 2008, Disfani et al 2011, Park & Chertov 2014. Depending on the type of waste material, the potential ways in which it could be used for economic purposes are as follows: building engineering, where it could be used as an additive in the production of concrete or as a binding material for the production of cement, replacing Portland cement clinker (Kinuthia & Nidzam 2011, Bilgin et al 2012, Dell'Orso et al 2012, Chen et al 2013, Helios-Rybicka et al 2013, Romero et al 2013, Alaibdo et al 2014; road engineering, where it can be considered as a material for soil stabilization, or to create road surfaces (Poon & Chan 2006, Engelsen et al 2012, Galvín et al 2013; agriculture, where it could be used as a fertilizer or to neutralize soil acidification (Harris & Lottermoser 2006, Mangwandi & Tao 2013, Tozsin et al 2014. Currently, broadly understood environmental protection is also considered to have an economic basis, as environmental standards need to be met.…”
Section: Introductionmentioning
confidence: 99%